Ageing in the Caribbean and the human rights of older persons : twin imperatives for action - Jones, Francis (UN ECLAC SantiagoCL, 2018)
Addresses the ageing of the Caribbean population and the situation with respect to the human rights of older persons. Considers the implications for public policy of these 'twin imperatives for action." Describes and explains the changing age structure of the Caribbean population. Looks at the progress that has been made in advincing and clarifying the human rights of older persons in international law.